Molecular serotyping and genotyping of penicillin non-susceptible pneumococci: the introduction of new sequence types, Tehran, Iran. (November 2019) - Azarsa, M.; Ohadian Moghadam, S.; Rahbar, M.; Baseri, Z.; Pourmand, M.R.
Abstract: The emergence of penicillin non-susceptible Streptococcus pneumoniae (PNSP) isolates can pose significant challenges to today's health-care system. Resistant clonal isolates are disseminated in different regions and countries, and this study was focused on the description of the epidemiological spread of these strains. Clinical samples were collected from individuals admitted to hospitals affiliated to the Tehran University of Medical Sciences, Iran. To investigate the molecular characteristics of PNSP isolates, they were subjected to molecular typing using multi-locus sequence typing (MLST). Serotype distributions of S. pneumoniae isolates were also evaluated by multiplex PCR assay. The most prevalent serotypes in the PNSP isolates were 23F, 19F, 14, 3 and 9V. Two isolates were considered as a non-vaccine serotype. The MLST analysis showed that PNSP isolates belonged to five different clonal complexes (CC180, CC217, CC81, CC63 and CC320) and 42% (5/12) of the sequence types were novel (12936, 12937, 12938, 12939 and 12940). This study indicates the high level of heterogeneity that is present among PNSP isolates. Unexpected high genetic diversity in small populations indicates consecutive diversification of resistant strains.